The Effect of Organic and Biological Fungicides on the Development of Ganoderma Fruiting Bodies - Widiastuti, Happy (International Journal of Oil Palm, 2025)
Ganoderma sp. is the main pathogen of oil palm that also attacks other plants such as rubber, eucalyptus, and acacia. Aside from being a pathogen, this fungus also lives saprobically. This study aims to examine the effect of organic fungicide on the growth of Ganoderma mycelia in vitro using Petri dish and the effect of organic fungicide and biofungicide on the development of Ganoderma fruiting bodies that grow on dead breadfruit trees. In testing on breadfruit wood, organic fungicide was given two times while for biological fungicide only one application for 3 consecutive days. The organic fungicide tested was effective in killing the growth of Ganoderma mycelium in vitro. The field test showed that after three weeks of organic fungicide application, the growth of fruiting bodies was inhibited while the control continued to develop and appeared enlarged. The growth of fruiting bodies treated continued to be inhibited until the second application of organic fungicide and this condition continued after application of trichoderma as biofungicide. At H65, there was higher population of bacteria on the control compared to treated fruiting bodies. On the 104th day, it can be isolated Ganoderma from the control but not from the treated fruiting bodies. These indicate that application of organic fungicide within 26th days has inhibited the growth of fruiting bodies and at 3.5 months, Ganoderma died. After 26th days of fruiting bodies breaking, there is new fruiting bodies from breadfruit wood control but not from the treated. This organic fungicide test needs to be specifically carried out again on fruiting bodies that grow on living plant stems to asses the effectivity as organic fungicide.